PENINGKATAN LITERASI KEAGAMAAN TATA CARA WUDHU PADA ANAK MELALUI VIDEO BASED LEARNING - Hairani, E.; Salimah, Z.R. (Buletin Udayana Mengabdi, 2024)
Religious literacy among children in Bojong Koneng, Bogor still needs to be improved especially related to understanding and practice of worship, such as ablution procedures. This community service activity aims to improve religious literacy through practical education on ablution procedures through video-based learning. The method used is qualitative with historical method and. The research results showed that 80% of children experienced an increase in their understanding of practicing proper ablution procedures. The involvement of parents and the community also contributed significantly to the success of this program. In conclusion, a fun and participatory educational approach not only helps children understand religious teachings, but also encourages them to practice them in their daily lives.